Optimizing Digital Assessment for English Language Learning - Sri Widiastuti Ida Ayu Made; I Gde Putu Agus Pramerta; Made Sita Paramita; Ni Putu Suryani Putri; Ida Ayu Praba Iswari Dewi; Ni Made Wik Pradani (Civiliza Publishing, 2026)
The growing incorporation of digital technology in education has revolutionized assessment procedures and presented new prospects for improving the evaluation of English language acquisition. The program sought to upgrade teachers' knowledge and practical skills in designing and executing digital assessment systems in English language classrooms. The training was based on the participatory method through interactive lectures, demonstrations, hands-on workshops, collaborative discussion and supervised practice on several digital assessment platforms. The program involved 20 teachers of English. Data were acquired via pre-test and post-test evaluations and semi-structured interviews; Quantitative analysis results indicated a considerable improvement in the competence of the participants with the mean score going up from 62.3 in the pre-test to 89.1 in the post-test suggesting significant advances in digital assessment knowledge and skills. Participants also showed enhanced skill in building digital assessment instruments, utilizing digital platforms, conducting formative assessment, and evaluating assessment data. Qualitative results also revealed that teachers have gained confidence in the integration of digital assessment into their classroom practices and saw the potential of digital assessment to enhance student engagement, to give fast feedback and to facilitate more effective evaluation of student learning. The findings underscore the necessity of ongoing professional development and long-term partnership between higher education and schools in the digital transformation of English language evaluation and enhancement of English language education.